The influence of social media marketing on brand equity with brand trust as mediation on Propolis Shampoo Products Pt Herba Penawar Alwahida Indonesia (Hpai-Hni) in Padang City - Muhammad Ilham; Whyosi Septrizola (Universitas Negeri Padang, 2023)
The purpose of this research is to analyze the effect of social media marketing on brand equity. In addition, this study also examines the mediating effect of brand trust on social media marketing, and brand equity. The population of this study is followers of HPAI-HNI official social media accounts who are Muslim and domiciled in West Sumatra. This study used a quantitative method and obtained 150 respondents through an online questionnaire with a purposive sampling technique. Data were analyzed using the PLS-SEM technique with SmartPLS 4. The results of this study are; (1) social media marketing has a significant effect on brand equity; (2) social media marketing has a significant effect on brand trust; (3) brand trust has a significant effect on brand equity; (4) social media marketing has no significant effect on brand equity through brand trust as an intervening variable.